ANALYSIS OF PRODUCT TYPES, PROMOTION AND CUSTOMER LOYALTY MEDIATED BY BRAND IMAGE AT PT. BANK MANDIRI (PERSERO) TBK - Kumala, Paramita Dewi; Wiyadi, Wiyadi; Nasir, Moechammad; Isa, Muzakar (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research endeavours to explore the influence of product categorisation and promotional strategies on consumer loyalty, with the brand image of Government bank serving as a mediating factor, along with conducting a thorough analysis. The study uses a quantitative approach to collect data by administering a questionnaire to the clientele of Government bank. The analysis of the data utilised structural equation modelling (SEM) along with statistical software. The findings of the study reveal that the type of product plays a crucial role in enhancing brand image, while advertising also significantly contributes to this enhancement. Furthermore, brand image is shown to be a key factor in fostering customer loyalty. Additionally, the type of product and marketing efforts are both significant in promoting customer loyalty, with brand image acting as a mediator in the relationships among product type, advertising, and customer loyalty.